Chronic lichenoid keratosis with good response to oral acitretin: a case report - Mariana S. Bernardes; Jéssica C. N. Araújo; Luísa L. Macias; Laísa E. de-Hollanda; Joelly T. L. Levermann; Alcidarta R. Gadelha; Patricia C. B. De Melo; Luciana Mendes-dos Santos (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Keratosis lichenoides chronica or Nekam's disease is a rare disease of unknown etiology and pathogenesis, with few cases described in the literature. The lichenoid-like lesions as well as their histopathological findings require a wide range of differential diagnoses. Its chronic, progressive course and refractoriness to topical and systemic therapies are hallmarks of this dermatosis. The aim of this report is to describe the case of a patient with typical cutaneous manifestations and compatible histopathological findings with a good response to acitretin.